Calculation of images of oriented C_60 molecules using molecular orbital theory - Hands, Ian D.; Dunn, Janette L.; Bates, Colin A. (Americal Physical Society, 2010)
Using Hückel molecular-orbital theory, images are created to represent the electron distributions expected for a C60 molecule adsorbed on a substrate. Three different orientations of the C60 molecule on the substrate are considered. The effect of the interaction of the molecule with the substrate is treated purely from the basis of symmetry using group theoretical methods. The resulting electron distributions are then used to generate idealized images which represent how the molecule may appear when observed in a scanning tunneling microscope (STM) experiment. Comparison is made with STM images appearing in the literature. It is found that the more complicated ab initio methods usually employed to simulate STM images are not required in order to match observed results. Furthermore, we find that an unequivocal identification of the orbitals responsible for a given STM image cannot be made from analysis of the STM image alone.